O papel do cirurgião dentista nas desordens do sono: ronco primário e apnéia obstrutiva do sono - Urbano, Igor Hoffman da Silva [UNESP] (2010)
Sleep disorders are today considered an etiological of various illnesses. Specialty medicine sleep comes increasingly worrying about improvement of quality of life through a refreshing sleep. The obstructive sleep apnea is the complete airway obstruction by the collapse of the tissues of Oropharynx, soft palate, and back of the tongue, for something around 10 s, with a frequency of at least 5 to 10 times per hour of sleep and characterised by deteriorating the quality of life of the patient. Snoring, also generally deteriorating social and family life of individuals. In chronic cases, the sleep apnea is responsible for causing hypertension, cardiac problems and even stroke. The treatment modalities ranging from behavioral changes of uvulopalatofaringoplastia surgeries. Recently, treatment through intra-oral devices has gained importance through research that prove the effectiveness of devices, that have specific characteristics. Intra oral appliances work by advance-mandibular, whereby the throat preclude tissues and enhance the region's musculature tonicidade. They are eminently in cases of mild and moderate apnéias. At the moment, is opening a new possibility for dentists, surgeons that with a correct positioning against multidisciplinarity of the problem, a broad assessment of the patient and using appropriate devices will surely gain ground in an area until then occupied only by doctors. This work have goals, submit revisions literary and report a clinical case of a patient who presented himself, after forwarding doctor complaining of snoring and porting the results of the examination of polysomnography. After analysis of clinical and complementary, was made an intra oral-appliance with a mandibular advancement on 70%. Clinical monitoring has shown excellent results in relation to patient comfort and likely elimination of snoring. The patient has adapted well to treatment and did not provide a single sign of Temporomandibular joint disorders-d